Notizie dal sito “Yi Dai Yi Lu” pindao in cinese e in inglese: un’analisi critica e comparativa - Natalia Francesca Riva (Geography Notebooks, 2018)
The promotion of the Belt and Road Initiative (BRI), a major China-led development and cooperation project launched in 2013, features among the centrepieces of China’s current political discourse and is one of the most closely-followed topics by both China’s and international audiences. The organization of the first Belt and Road Forum for International Cooperation (BRF) held in Beijing on May 14-15 2017 generated a considerable mediatic echo in which Xinhua News Agency played a relevant role. This paper focuses on the website “Yi Dai Yi Lu” pindao (“一带一路”频道), the online space dedicated to the BRI by the state-subordinated agency. The examination offers a comparative analysis of a selection of news titles published over the period of the BRF in the Chinese and English editions of this website. The aim is to examine the narrative constructed therein by offering a two-fold examination of how and to what extent: (1) Xinhua’s institutional and entrepreneurial identity influences its news production; and (2) the nature of different audiences affects the representations of the BRI and BRF in discourses targeted by the same producer to a Chinese-speaking or English-speaking audience.